2020
DOI: 10.1108/itp-04-2019-0156
|View full text |Cite
|
Sign up to set email alerts
|

How the social dimension of fitness apps can enhance and undermine wellbeing

Abstract: Purpose While the positive health benefits of fitness apps, which motivate and track physical exercise, are widely acknowledged, the adverse connection between these technologies and wellbeing has received little attention. The purpose of this paper is to determine how the social dimensions of fitness apps predict the type of passion (harmonious and obsessive) one has for physical exercise, and what the resulting positive and negative implications are for wellbeing. Design/methodology/approach Drawing from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 89 publications
(197 reference statements)
3
46
0
Order By: Relevance
“…Hamari and Koivisto (2015) find that recognition can contribute to positive attitude and then drive continued use of gamified exercise services. Whelan and Clohessy (2020) indicate that recognition from fitness application is positively associated with user's passion. In gamified services, recognition can induce users' desire for social comparison that will provide user value and increase firm-beneficial user behaviors.…”
Section: The Research Model and Hypothesesmentioning
confidence: 95%
See 3 more Smart Citations
“…Hamari and Koivisto (2015) find that recognition can contribute to positive attitude and then drive continued use of gamified exercise services. Whelan and Clohessy (2020) indicate that recognition from fitness application is positively associated with user's passion. In gamified services, recognition can induce users' desire for social comparison that will provide user value and increase firm-beneficial user behaviors.…”
Section: The Research Model and Hypothesesmentioning
confidence: 95%
“…In the IS research studies, it is widely acknowledged that users pursue positive recognition from others when they make use of interactive ICT tools (Hwang and Francesco, 2004). With the penetration of social features in IS, studies have indicated that recognition could result in positive outcomes such as attitude, use and continued use toward various systems (Hernandez et al , 2011; Teng, 2017), including gamified services (Whelan and Clohessy, 2020; Hamari and Koivisto, 2015; Wolf et al , 2020).…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, obsessive passion reflects a lack of self-control towards engaging in the activity. The same athlete would display an obsessive passion if they were consumed by a sense of having to persist with their planned 10km run no matter what else might be going on in their life (e.g., feeling ill, recovering from injury, or a family or work event), and thus often leads to maladaptive outcomes (Curran, Hill, Appleton, Vallerand, & Standage, 2015;Whelan & Clohessy, 2020). Obsessive passion emerges from a partial behavioral integration of the activity that one loves (Curran et al, 2015).…”
Section: The Dualistic Model Of Passionmentioning
confidence: 99%